1994
DOI: 10.1590/s0074-02761994000400002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C prevalences among blood donors in the south region of Brazil

Abstract: The prevalence of hepatitis B and C infection has been determined in a seroepidemiological survey among blood donors from the south of Brazil (Florianópolis, State of Santa Catarina). These markers has also been correlated with the levels of alanine aminotransferase (ALT), a surrogate marker to prevent post-transfusion hepatitis. Sera from 5000 donors were randomly collected in the period of April to November 1991. The prevalences of HBsAg, anti-HBs and anti-HBc were respectively 0.78%, 7.02% and 13.98%. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
4
11
0
3
Order By: Relevance
“…Abnormal levels of ALT were found in 11 individuals (2%). The HBsAg prevalence was similar to that recorded in the city of Florianópolis, State of Santa Catarina, by Vasconcelos et al (1994). According to Zuckerman (1985), this HBsAg prevalence is consistent with a low prevalence pattern of HBV infection (0.2-0.5% HBsAg).…”
supporting
confidence: 83%
“…Abnormal levels of ALT were found in 11 individuals (2%). The HBsAg prevalence was similar to that recorded in the city of Florianópolis, State of Santa Catarina, by Vasconcelos et al (1994). According to Zuckerman (1985), this HBsAg prevalence is consistent with a low prevalence pattern of HBV infection (0.2-0.5% HBsAg).…”
supporting
confidence: 83%
“…The prevalence of positive serology for viral hepatitis found in this study is similar to those reported previously for Brazil by other authors (HBsAg: 0.14-0.78%, anti-HBc: 2.05-13.44%, anti-HCV: 0.34-1.14%) [46][47][48] . The prevalence of hepatitis B markers in Brazil varies greatly by region.…”
Section: Discussionsupporting
confidence: 91%
“…This data compares to blood donors studies (0.86%) in Rio de Janeiro (Vanderborght et al 1993) and in southern Brazil (0.28%) (Vasconcelos et al 1994). In a study with AIDS patients in São Paulo (Gir et al 1994) the rate was similar (30%).…”
Section: Resultssupporting
confidence: 62%
“…Morever, the absolute number of AIDS (Clara Yoshida, personal communications). The HBsAg rate (3.7 in HIV negative and 9.1 in HIV positive volunteers) was also higher than that found among blood donors in Rio de Janeiro (Vanderborght et al 1993) and southern Brazil (Vasconcelos et al 1994) where rates were 1.6 and 0.78, respectively. In a study with patients with AIDS from São Paulo (Gir et al 1994) this rate was 33% and in Europe (Lemp et al 1994) the rate was 20%.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation